Effect of Qingyangshen glycosides on social defeat mice model. (15th July 2022) - Liu, Dingding; Wang, Jingru; Chang, Lulu; Zhu, Qiang; Jiang, Ning; Azhar, Mudassar; Zeng, Guirong
Abstract: Ethnopharmacological relevance: Qingyangshen ( Cynanchum otophyllum C.K.Schneid.PI.Wilson.) is the folk medicine of Yunnan which is renowned for its use in the management of neuropsychiatric diseases. The isolated glycosides from Qingyangshen have demonstrated relief in the social defeat stress, however, mechanism of action has not yet been elucidated. Aim of the study: This study is aimed to elucidate the effect of Qingyangshen glycosides (QYS) on chronic social defeat stress (CSDS)-induced depression-like symptoms and the related mechanism. Materials and methods: In mice, CSDS model was developed, and the effect of QYS was evaluated by observing the behavioral performance of these mice exposed to tasks related to depression-like activities. Moreover, microscopic pathological examinutesation was also done. Furthermore, the protein expressions related to social defeat stress were also determined to elucidate the possible underlying mechanism. Results: Our results indicated that QYS treatment reversed the CSDS-induced depressive-like behaviors as measured by the increased sucrose preference, open field activity, and social interactions among mice. The reversal of the morphological changes in the hippocampus of the CSDS mice was also noted. Additionally, QYS treatment also upregulated the silent mating type information regulation 2 homolog 1 (SIRT1), peroxisome proliferator–activated receptor-γ coactivator-1α (PGC-1α), fibronectin III domain containing protein 5 (FNDC5), brain-derived neurotrophic factor (BDNF), tropomyosin-related kinase B (TrkB), and mitogen-activated protein kinase (MAPK) proteins. Conclusions: Our study indicated that QYS had a good anti-social defeat stress effect on CSDS-induced depression in mice, mainly through SIRT1/PGC-1α/FNDC5/BDNF-TrkB signaling pathway activation. Graphical abstract: Image 1